2022
DOI: 10.3390/pharmaceutics14020274
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Drug Delivery via Zein In Situ Forming Implants Augmented with Titanium-Doped Bioactive Glass for Bone Regeneration: Preparation, In Vitro Characterization, and In Vivo Evaluation

Abstract: In situ forming implants (IFIs) are non-surgical approach using biodegradable polymers to treat bone fractures. The study aimed at preparing dual-drug-loaded IFIs to deliver pitavastatin (osteogenic drug) and tedizolid (antibiotic) using zein as the implant matrix via solvent-induced phase inversion method. At first, several investigations were done on pitavastatin-loaded zein IFIs, where three concentrations of zein were used (10, 20, and 30% w/v). IFIs were evaluated for their solidification time, rheologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…The STF was prepared by dissolving NaCl (3.4 g), NaHCO 3 (1.1 g), KCl (0.7 g), and CaCl 2 ·2H 2 O (0.04 g) in 500 mL of Milli-Q ® water. A dialysis bag was used as a release barrier [ 41 ]. Around 1 mL of F2 suspension (~821.5 µg of TZP) was put into the dialysis bags, and both ends of the bags were tied with threads.…”
Section: Methodsmentioning
confidence: 99%
“…The STF was prepared by dissolving NaCl (3.4 g), NaHCO 3 (1.1 g), KCl (0.7 g), and CaCl 2 ·2H 2 O (0.04 g) in 500 mL of Milli-Q ® water. A dialysis bag was used as a release barrier [ 41 ]. Around 1 mL of F2 suspension (~821.5 µg of TZP) was put into the dialysis bags, and both ends of the bags were tied with threads.…”
Section: Methodsmentioning
confidence: 99%
“…Though it lacks a cell proliferative effect, so blending zein with bioactive substances (e.g. bioceramics, calcium phosphates, and osteoinductive drugs) is preferred to support the proliferation and differentiation of bone cells [ 82 , 89 , 90 ].…”
Section: Biomaterials In Tissue Engineeringmentioning
confidence: 99%
“…The fabricated implant showed a sustained release of both drugs for 28 days. In vivo studies on Sprague Dawley rats demonstrated a significant bone regenerating effect [ 82 ]. This study succeeded to introduce zein as a promising implant matrix; however, more studies and investigations should be conducted to optimize the fabricated implant to be applicable for large-sized bone defects.…”
Section: Biomaterials In Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatrics, geriatrics, and disabled patients also require special treatment to enhance their adherence to their therapy. Implantable drug delivery systems could introduce a good solution (Abdel-Salam et al., 2020 ; Kamel et al., 2020 ; Eldeeb et al., 2022 ) to avoid fluctuating drug levels and sustain its release, hence increasing therapeutic effect and patient compliance (Ainslie & Desai, 2008 ; Elkasabgy & Mahmoud, 2019 ). Transdermal drug delivery systems, such as microneedles are designed to deliver the skin through the bloodstream (Alkilani et al., 2015 ).…”
Section: Innovative Strategies For the Preparation Of Micro/nanofluid...mentioning
confidence: 99%